THE DEVELOPMENT OF SAN LUIS POTOSIIRAL STRUCTURE IN A GALAXY - PISMIS, P (UNAM, Observatorio Astronómico Nacional, CD MEXICO, DF, MEX, 1962)
The main aim of this paper is to show that by postulating the existence of a rotating and shrinking gaseous bulge with a magnetic field as envisaged, and given a rotation curve, a galaxy will have produced and maintained spiral arms during a reasonably lo
BOL OBS TONAN TACUB
Keywords: DEVELOPMENT, SPIRAL STRUCTURE, GALAXY; ASTRONOMIA Y ASTROFISICA; COSMOLOGIA Y COSMOGONIA; GALAXIAS